Correlation between Internal Jugular Vein Tunnel Cuffed Catheter Tip Position as Hemodialysis Access with Suspected Catheter Related Bacteremia and Related Risk Factors at RSCM 2018–2019 - Pratomo, Susatyo J; Muradi, Akhmadu (UI Scholars Hub, 2019)
Introduction. Infection is the main complication of prolonged–term catheter uses as hemodialysis access. The KDOQI recommends the insertion of tunnel venous hemodialysis catheter in the right internal jugular vein (IJV) where the tip placed in the right atrium and the arterial opening enfacing the mediastinum. The previous study showed that the incidence of catheter–related bacteremia (CRB) is 35% at three months' use and 54% at six months' use. The TCC tip position as hemodialysis access in left IJV is correlated more to dysfunction and infection compared to the right IJV. Method. A cross–sectional study was conducted with 62 subjects of hemodialysis patients using IJV TCC access. Data of TCC site of insertion, TCC tip position, suspected CRB, and subject’s characteristics including age, sex, and diabetes mellitus from January 2018 to January 2019 collected from medical records. The correlation between these variables analyzed using Chi–Square test with a p–value of Results. Out of 62 subjects enrolled in this study, 45 (72.6%) were 60 yr. or less, forty (66.1%) males, fifteen with diabetes mellitus as the comorbid (24.2%). Thirty–nine subjects (62.9%) TCC tip positioned in SVC, two subjects (3.2%) in CAJ, and 21 subjects (33.9%) in RA. Twenty–two of these 62 with suspected CRB (35.48%). There is no significant correlation between the TCC tip position with suspected CRB incidence (p = 0.92, OR 1.05, 95% CI = 0.35 – 3.08). Age, gender, and diabetes mellitus were not statistically proven as risk factors of suspected CRB. Conclusion. There is no significant correlation between the TCC tip position and studied risk factors with suspected CRB.